An efficient and rapid in vitro regeneration system for metal resistant cotton - Biçakçi, E; Memon, AR (ACAD SCIENCES CZECH REPUBLIC, INST EXPERIMENTAL BOTANY, 2005)
In this report we describe the most suitable protocol for callus formation and plant regeneration for cotton. We screened 15 cotton (Gossypium hirsutum L.) genotypes for metal resistance and two of them, Nazilli M-503 (M503) Nazilli 143 (N-143) selected as Cd, Cu and Ni resistant. The cotyledonary nodes from these genotypes were the best explants for regeneration of shoots (more than 90 %) and roots (50 to 70 Shoot apex also gave good shoot regeneration (more than 90 %) but their root regeneration efficiency was low (35 These results show that Murashige and Skoog (MS) media containing 0.44 mu M naphthaleneacetic acid (NAA) and 0.98 mu M indole-3-butyric acid (IBA) was the most suitable recipe for getting high shoot and root regeneration from cotyledonary nodes of N-143 and M503 cotton genotypes.
Keywords: callus; Gossypium hirsutum; heavy metal tolerant plants; plant regeneration; FREQUENCY SOMATIC EMBRYOGENESIS; PLANT-REGENERATION; Plant Sciences